Analisis Kesalahan Mahasiswa PGSD pada Tugas Aljabar Sederhana Mata Kuliah Konsep Dasar Mapel Matematika SD - I Komang Sesara Ariyana (Cetta: Jurnal Ilmu Pendidikan, 2020)
This study aimed to identify the errors of PGSD students on simple algebra assignments on Basic Concept of Elementary Mathematics Subject at STAHN Mpu Kuturan Singaraja. The subjects of this study were Semester II PGSD students of STAHN Mpu Kuturan Singaraja in the academic year 2019/2020 as many as 11 people. Errors in mathematics in this study were divided into factual errors, procedural errors, and conceptual errors. This type of research was a quantitative descriptive study. The data collection method used was a test. The test instrument used was a concept understanding test to be able to find students' errors. A total of 20 items in the test were validated by two experts with the Lawshe’s CVR technique. The results showed that (1) the general error rate of PGSD study program students on Simple Algebra assignment on Basic Concept of Elementary Mathematics Subject was 30.26% in the low error category, (2) there was the highest error of 43% (error category moderate) and lowest 16% (very low error category), 3) factual errors ranged from 10% - 20% (very low category), 4) procedural errors ranged from 7% - 53% (very low category to medium category), and 5) conceptual errors ranged from 35% - 65% (low to high categories).